Дослідження Вишгорода у 1936 р. - Капустін, К.М. (Археологія і давня історія України, 2020)
Проаналізовано архівні й фондові матеріали з розкопок Вишгорода 1936 р., уточнено хронологію, місце розташування житлових, господарських споруд і поховальних комплексів, а також датування речових знахідок із культурно-хронологічних горизонтів давньоруського, золотоординського та нового часів. The archives and archaeological materials from excavations in Vyshgorod in 1936 are analysed in the paper. This year the large-scale excavations were conducted on the territory of the old city: near the church of st. Borys and Hlib, two sites in the northeast part of the hillfort and few trenches in different parts of the town. The obtained results correlate with the reports of the narrative sources and indicate the significant development of the city in the period from the 11th to the mid-13th century.